2022
DOI: 10.1002/lary.30341
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Blood Transfusion in Head and Neck Cancer Revisited

Abstract: Objective To reevaluate the frequency of perioperative blood transfusion, transfusion triggers, and survival impact in patients with incident, surgically treated head and neck cancer (HNC) in restrictive transfusion regimens. Methods Retrospective analysis of surgically treated patients with incident HNC with and without perioperative blood transfusion between 2008 and 2019 at the Department of Otorhinolaryngology, Head and Neck Surgery, Medical University of Innsbruck, according to the department's clinical H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Inclusion criteria were histologically confirmed squamous cell carcinoma of the oropharynx, known high risk HPV-status by p16 immunohistochemistry [ 22 ], and patient consent to use anonymized data and tissue samples for scientific investigations and publications. A commercial in vitro diagnostic certified assay containing a ready-to-use prediluted mouse monoclonal antibody was used for p16 detection (CINtec® Histology V-Kit, Roche Ventana, Tucson, AZ, USA) [ 23 ]. The definition of an HPV + tumor was based on the overexpression of p16.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were histologically confirmed squamous cell carcinoma of the oropharynx, known high risk HPV-status by p16 immunohistochemistry [ 22 ], and patient consent to use anonymized data and tissue samples for scientific investigations and publications. A commercial in vitro diagnostic certified assay containing a ready-to-use prediluted mouse monoclonal antibody was used for p16 detection (CINtec® Histology V-Kit, Roche Ventana, Tucson, AZ, USA) [ 23 ]. The definition of an HPV + tumor was based on the overexpression of p16.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased OS, increased wound infections, flap failures, and hospital readmission rates were all found to be associated with perioperative blood transfusions 198,201–203 . A recent study published by Runge et al concluded that current transfusion practices do not increase oncologic risk or decrease OS over a 5 year period; however, this study included only a limited number of patients 204 …”
Section: Resultsmentioning
confidence: 90%
“… 198 , 201 , 202 , 203 A recent study published by Runge et al concluded that current transfusion practices do not increase oncologic risk or decrease OS over a 5 year period; however, this study included only a limited number of patients. 204 …”
Section: Resultsmentioning
confidence: 99%